MUT'AH IN MODERN MUSLIM FAMILY LAW. Study of Legislation in Syria, Egypt and Indonesia - Safira Mustaqila; Yuni Roslaili (Universitas Islam Negeri Ar-Raniry, 2022)
The reality showed that there are still many injustices against women that can occur anywhere, including in the domestic sector, as well as in Muslim countries. Therefore reform of Muslim family law is seen as necessary because it plays an important role in the protection of women and children and the fulfillment of their rights. Mut’ah is a gift from a husband to his ex- wife after a divorce, including one of the areas reformed in a number of Muslim countries, including in Syria, Egypt and Indonesia. Mut’ah is a gift from a husband to his ex- wife after a divorce is one of the areas reformed in a number of Muslim countries including in Syria, Egypt and Indonesia. The results of the study found that there had been reform of Muslim family law regarding mut’ah in the three countries studied, namely Syria, Egypt and Indonesia. if in traditional literature( fiqh) the right of mut’ah is only obligatory to be given to a divorced wife before had sex and with a dowry that has not been given, but in the three countries studied regardless of whether the wife was divorced before had sex or after had sex and whether the dowry has been determined or not. In addition, in modern Muslim family law there are provisions for the maximum limit of mutah that a husband must give to his wife, such as the standard of living for three years in Syria and two years in Egypt while in fiqh it is determined that the maximum size of mut’ah is not to exceed half the mistsil dowry or the price of a slave.